The Eclectic Approach application: A review study of English teaching experiences - Bonilla Tenesaca, Josué; Egas Herrera, Diana; Campoverde López, Johnny (Arandu UTIC, 2025)
This article aimed at providing a review study of English teaching experiences where the eclectic approach could be used to support language teaching. The analytical-synthetic, inductive-deductive and hermeneutic-dialectical methods are used for the analysis and interpretation of the data processed, derived from the bibliography consulted and pedagogical experiences in this field. The document study method and a registration instrument were also used for the review study of English teaching experiences. English teaching experiences were selected from a group of 21 professors that attended the Masters´ Degree Program Pedagogy of English as a Foreign Language at the University of Ecuador (UBE) since 2022, they were all members of Group 1. From 72 practical tasks developed in the course Second Language Acquisition, 21 were selected from Unit 1, dealing with methods, approaches and techniques in Foreign Language Teaching (FLT). They were selected for the review study using some inclusion criteria and coded into the methods integration dimension, the language skills integration dimension and the didactic dimension. The indicators permitted to verify quantity of methods integrated in the classrooms, integration of linguistic skills, and didactic planning. The review study showed the tendencies to integrate several methods as a way to use an eclectic approach. It also provided useful information for participants regarding the application of the eclectic approach in English language teaching. The study contributes to highlight positive learning outcomes with the use of the eclectic approach to be considered in future research.